Vetrolomi konec junija 2006 - razvoj vremena in posledice - Sinjur, Iztok (Gozdarski vestnik, 2007)
At the end of June 2006, following two hot and dry weeks, severe thunderstormswith hail and strong wind occurred. The first storm hit the countryside near Ruše in the forenoon, and in the afternoon a much bigger multicell system in parts of western and central Slovenia built up. It caused various damage on the local scale, with hail and two larger windthrows. The largest windthrow occurred on the Jelovica plateau and a smaller one near Ptuj. The article shows weather development before and on that day, presentingwindhrows and their consequences.
Keywords: vetrolomi; gozdovi; vreme; weather; nevihte; posledice